2017
DOI: 10.1038/ncomms15966
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and expression quantitative trait loci studies identify multiple susceptibility loci for thyroid cancer

Abstract: Thyroid cancer is the most common cancer in Korea. Several susceptibility loci of differentiated thyroid cancer (DTC) were identified by previous genome-wide association studies (GWASs) in Europeans only. Here we conducted a GWAS and a replication study in Koreans using a total of 1,085 DTC cases and 8,884 controls, and validated these results using expression quantitative trait loci (eQTL) analysis and clinical phenotypes. The most robust associations were observed in the NRG1 gene (rs6996585, P=1.08 × 10−10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 62 publications
5
78
0
Order By: Relevance
“…Much effort has been made to identify such susceptibility variants. The most robust evidence is for markers at 9q22.33 (FOXE1), 14q13.3 (NKX2-1), 2q35 (DIRC3) and 8p12 (NRG1), as variants in these regions have been repeatedly associated with DTC through several genome-wide association studies (GWASs), confirmed in follow-up studies and independently replicated across different populations (6)(7)(8)(9)(10)(11)(12). Additional markers have recently been suggested (8,(10)(11)(12)(13) but still require confirbut still require confirmation and replication.…”
Section: Introductionmentioning
confidence: 75%
“…Much effort has been made to identify such susceptibility variants. The most robust evidence is for markers at 9q22.33 (FOXE1), 14q13.3 (NKX2-1), 2q35 (DIRC3) and 8p12 (NRG1), as variants in these regions have been repeatedly associated with DTC through several genome-wide association studies (GWASs), confirmed in follow-up studies and independently replicated across different populations (6)(7)(8)(9)(10)(11)(12). Additional markers have recently been suggested (8,(10)(11)(12)(13) but still require confirbut still require confirmation and replication.…”
Section: Introductionmentioning
confidence: 75%
“…TTF1 levels from 3 independent experiments were quantified with ImageJ software. *P , 0.05, **P , 0.01 compared to 0 h. In addition to normal HTori3 cells, TTF1 expression has been found in a variety of thyroid tumor cells, such as follicular adenomas, follicular carcinomas, and papillary carcinomas (10)(11)(12). We observed that TTF1 expression levels were divergent in these cells.…”
Section: Discussionmentioning
confidence: 58%
“…TTF1 is important for regulation of TG, thyroid peroxidase (TPO), and thyrotropin receptor (TSHR) expression (1,8,9). Among thyroid tumors, TTF1 is expressed in all tumors of follicular derivation, such as follicular adenoma and follicular and papillary carcinoma (10)(11)(12). The C-cell-derived medullary carcinomas are positive for TTF1 immunoreactivity (13,14).…”
mentioning
confidence: 99%
“…For DTC, 31 associations have been reported (Tab. I) [20][21][22][23][24][25][26][27]. SNPs uncovered by GWAS are located on 12 chromosomes in 17 different loci.…”
Section: Reviewmentioning
confidence: 99%